Community Diagnosis Permasalahan Kesehatan di RT 08, Dusun Pringgolayan, Kelurahan Banguntapan, Kapanewon Banguntapan, Kabupaten Bantul, DIY - Rosita, Diah Ayu; Zulkarnain, Ahmad Aditya Sidik; Widiantika, Maradella; Zafirah, Kamilah; Safitri, Diah; Fauzi, Amir (FKM UIN Sumatera Utara Medan, 2024)
Community Diagnosis is an activity to explore the presence of health problems in a group of communities or society by collecting data directly in the field. The data obtained from the field is then processed and analyzed and then followed by interpretation. The next step is to determine the priority of the problem with the aim of getting an overview of health problems in the RT. 08, Pringgolayan Village, Banguntapan, Bantul. The method used in this activity was quantitative descriptive analysis using door to door interviews using a diagnostic questionnaire which was then intervened with counseling and the provision of health promotion media in the form of posters, leaflets and checking blood pressure. Based on the normality test that has been carried out, the data is normally distributed, so it is continued with the paired sample t test (two mean difference test) obtained a significance value of 0.000, which means <0.05 so it can be concluded that there is a difference in the average knowledge about the dangers of smoking between before and after smoking and after